Supplementation with nutraceuticals produces changes in working horse’s blood parameters but not in their body composition - Manso Filho, Hélio Cordeiro; Abreu, José Mário Girão; Manso, Helena Emília Cavalcanti da Costa Cordeiro; Magalhães, Fernando Jorge Rodrigues (Acta Scientiae Veterinariae, 2018)
Background : : : : There is little scientific data about the effects of continuous supplementation with nutraceuticals over horse’s health and performance. Horse owners and veterinarians are still using supplements for horses without any kind of evaluations. At the Brazilian market is possible to buy hundreds of different products, but there is not private or state regulation over production and quality of these products. The absence of information about quality and efficacy of these products may contribute to mistakes in horse’s nutrition program. The objective of this research was to determine the effect of supplementation with a combination of nutraceuticals over some blood parameters (red cell count, total plasma proteins, free plasma glutamine and glutamate) and components of body composition in working horses. Materials, Methods & Results: There were 19 gelding horses, divided in two groups: nutraceutical (NUTR; n=10) and placebo (PLAC; n=9). Both groups received equivalent feeding regimens in regard to concentrate and grass, and did similar exercise program. NUTR group received their pellets with nutraceuticals, and PLAC group received a placebo during the morning meal. There is no visual difference between nutraceutical and placebo pellets. Body composition determination and blood collection were taken in three periods: pre-test, after 4 and 12 weeks of supplementation. Body composition was determined after evaluation of horse’s body mass by electronic scale associated with measurement of rump fat by ultrasound. Results showed that there were no significant changes in body composition during 12 weeks of supplementation in both groups, which had percentage of body fat around 13%. However, supplementation with nutraceutical produced significant changes (P<0.05) in some blood parameters in NUTR group. This group had large red cell count, hematocrit and blood glutamine concentration when compared with PLAC group after 12 weeks of supplementation. Blood glutamate concentration did not change in both groups. Discussion: Supplementation with nutraceutical or placebo did not produce illness or other nutritional problem in the experimental horses during 12 weeks. Also, because the nutraceutical and placebo pellets were visually similar to horse’s grain, the experimental animals did not have problems to eat all feed during 12 weeks. During this period it was observed that NUTR group had some improvement of the blood parameters when compared with PLAC group (P<0.05), without adaptation or changes in body mass. Frequently supplement’s advertises use improvement in the body mass as major effects of their products, but some of these effects are subjective because they use body score to show supplementation’s results. Increase in hematocrit (>16%), total plasma protein (>7%) and free plasma glutamine (>20%) observed in NUTR group will contribute to horse’s performance since it is positive action on red blood indexes and plasma amino acid concentration, contributing to the well-being of this horse group. Increase in blood glutamine concentration observed in NUTR group without improvement of body composition was not expected because this amino acid is produced mainly by skeletal muscle. Increase in fat-free mass frequently is associated with improvement of blood glutamine concentration. Finally, initial elevation in few parameters in PLAC group at 4 weeks of supplementation probably was associated with improvement of general management practices. In conclusion, Supplementation with a nutraceutical combination, for 12 weeks, produces changes in the concentration of some blood parameters, but it didn’t modify the corporal composition. The elevation of those components can favor the transport of oxygen and nutrients in tissues leading to improvement in the horse performance.